EPID-14. POPULATION-BASED ANALYSIS OF DEMOGRAPHIC AND SOCIOECONOMIC DISPARITIES IN PEDIATRIC CNS TUMOR SURVIVAL IN THE UNITED STATES. Issue 2 (22nd June 2018) - Zahedi, Shadi; Fineberg, Robert; Eguchi, Megan; Cockburn, Myles; Green, Adam
Abstract: INTRODUCTION: Malignant central nervous system (CNS) tumors are the most common cause of childhood cancer mortality. Minority race/ethnicity and socioeconomic disadvantages have been established as risk factors for poorer outcomes in adult and pediatric cancers; however, these issues are understudied in brain tumors. We investigated demographic and socioeconomic risk factors for poorer survival in childhood CNS tumors. METHODS: We used the Surveillance, Epidemiology, and End Results (SEER) 18 registries to obtain overall survival (OS), stage, demographic, insurance, and socioeconomic (by census tract) data on children 0-19 years old at diagnosis of malignant CNS tumors (ependymoma, glioma, medulloblastoma, other embryonal (PNET/pineoblastoma/ATRT), and unspecified/other) from 2000-2013. Univariate and multivariable analyses were performed. RESULTS: On multivariable analysis, Black (HR 1.381, p=0.0038) and Hispanic (HR 1.215, p=0.043) patients showed poorer OS overall than White and non-Hispanic patients, respectively. Black patients with glioma and ependymoma also had significantly poorer OS than White patients. Medulloblastoma patients living in language isolated areas, and other embryonal tumor patients living in high poverty areas, had significantly poorer OS than those living in low language isolation and low poverty areas, respectively. We did not find a higher likelihood of metastatic disease at diagnosis for these groups. However, many of the OS disparities were still present when patients were subgrouped by local/metastatic disease, suggesting potential treatment disparities. CONCLUSIONS: Disparities in OS of pediatric brain tumors exist based on race, ethnicity, and some socioeconomic factors. Our subsequent efforts will attempt to isolate and address specific causes of these disparities.